2017
DOI: 10.1084/jem.20161674
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic antiproliferative activity of the innate sensor STING in T lymphocytes

Abstract: The innate sensor STING is critical for innate immune activation, but its role in adaptive immunity is unknown. By studying pathogenic mutations in STING found in patients, Cerboni et al. show that active STING inhibits proliferation in T lymphocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
238
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(264 citation statements)
references
References 42 publications
25
238
0
1
Order By: Relevance
“…Interestingly, the most frequent virus isolated was rhinovirus, which may be a direct consequence of effective type I IFN inhibition by ruxolitinib at least in respiratory epithelial cells, where IFN-β is required to control rhinovirus [16,17]. On the other end, these infections might result from a cumulative effect of the drug with the reported developmental and in vitro proliferative defects of STING mutant T lymphocytes [18,19]. Considering the severity of lung disease and the lymphopenia ( Table 2) present before ruxolitinib treatment, P2 was started on antibiotic prophylaxis with Bactrim and Azithromycin; that, however, did not seem to prevent the febrile episodes, mostly if not always caused by viral pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the most frequent virus isolated was rhinovirus, which may be a direct consequence of effective type I IFN inhibition by ruxolitinib at least in respiratory epithelial cells, where IFN-β is required to control rhinovirus [16,17]. On the other end, these infections might result from a cumulative effect of the drug with the reported developmental and in vitro proliferative defects of STING mutant T lymphocytes [18,19]. Considering the severity of lung disease and the lymphopenia ( Table 2) present before ruxolitinib treatment, P2 was started on antibiotic prophylaxis with Bactrim and Azithromycin; that, however, did not seem to prevent the febrile episodes, mostly if not always caused by viral pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent STING signaling reportedly affects T cell function as well. T cells isolated from patients with constitutively activating STING genetic mutations had fewer circulating memory T cells . Based on this biology, STING agonists have also been evaluated as a potential therapeutic agent for T cell malignancies.…”
Section: Basic Biology Of the Sting Pathwaymentioning
confidence: 99%
“…T cells isolated from patients with constitutively activating STING genetic mutations had fewer circulating memory T cells. 94 Based on this biology, STING agonists have also been evaluated as a potential therapeutic agent for T cell malignancies. Interestingly, STING agonists delayed tumor growth of T-ALL murine tumors even in STING-deficient hosts, suggesting tumor-intrinsic STING activation could have beneficial anti-tumor effects in T-lineage malignancies.…”
Section: Cell Type-specific Effects Of Sting Signalingmentioning
confidence: 99%
“…While extracellular cGAMP signaling in M1 macrophages and NK cells resulted in increased IFN-I production, extracellular cGAMP signaling was toxic to T cells when combined with ionizing radiation. There is a substantial body of evidence linking STING activation to immune cell death or antiproliferation (Cerboni et al, 2017;Gaidt et al, 2017;Gulen et al, 2017;Larkin et al, 2017;Tang et al, 2016); indeed, 2'3'-CDA S , one of the cGAMP analogs in clinical trials, has a narrow therapeutic window due to T cell ablation at higher doses (Sivick et al, 2018). Consequently, the impact of STING signaling on T cell viability should be considered when combining radiation, STING agonists, and/or CTLA-4/PD-1 checkpoint inhibitor therapies, which are dependent on T cells for their efficacy (Blank et al, 2004;Iwai et al, 2002;Leach et al, 1996;Shrikant et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…While cGAMP leads to a strong IFN-I response in some cell types, there is mounting evidence that the effects of cGAMP signaling are cell-type specific. For example, it has been shown that T cells die in response to cGAMP signaling (Cerboni et al, 2017;Gulen et al, 2017;Larkin et al, 2017). Additionally, a recent study showed that cGAMP signaling in different cell types in the mouse lung led to different levels of IFN-I production, with some cell types unable to produce enough IFN-I for effective immunity (Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%